2006
DOI: 10.1021/jp057383d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cation on Charge Recombination in Dye-Sensitized TiO2 Electrodes

Abstract: The reaction of a dye cation recombining with an electron in TiO(2), in the presence of Li(+), Ca(2+), and TBA(+) cations, was studied with laser-induced transient absorption measurements. The active cations, Li(+) and Ca(2+), shorten the dye cation lifetime on sensitized TiO(2) but not ZnO electrodes. By combining the absorbance measurements of the dye cation with simultaneous measurements of the current transient, the contribution of the recombination reaction to the current is identified. Furthermore, class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…For example, low coverages of water on TiO 2 have been shown to promote electron injection from excited dyes and sensitizers [637,658,1324], presumably by favorably modifying the electrostatics at the injection site. Water, as a solvent, can provide hydrogen-bonding networks that assist in: stabilizing surface species important in O 2 photoreduction [820], minimizing depletion of important surface species (such as O 2 ) that result from photodesorption [201], or stabilizing excited electrons in surface states [192][193][194][195][196].…”
Section: Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, low coverages of water on TiO 2 have been shown to promote electron injection from excited dyes and sensitizers [637,658,1324], presumably by favorably modifying the electrostatics at the injection site. Water, as a solvent, can provide hydrogen-bonding networks that assist in: stabilizing surface species important in O 2 photoreduction [820], minimizing depletion of important surface species (such as O 2 ) that result from photodesorption [201], or stabilizing excited electrons in surface states [192][193][194][195][196].…”
Section: Promotermentioning
confidence: 99%
“…In some cases, the ability of adsorbed metal cations to scavenge CB electrons had a negative effect on O 2 photoreduction, particularly when the reaction products of O 2 photoreduction were needed to promote indirect oxidation processes [230,1288,1461]. Adsorbed cations have been shown to inhibit back-electron transfer in DSSC situations [1324,1462,1463]. The presence of cationic species (e.g., Mg 2+ , Li + , Na + and K + ) at the surface of TiO 2 stabilized I − at or near the surface, enhancing its rate of oxidation (by a photoionized dye) in DSSC applications [1463].…”
Section: Metal Cationsmentioning
confidence: 99%
“…Most of these charge transport processes occur at the semiconductor/ electrolyte solution interface, and it was reported that the constituents in the electrolyte solution such as cation and redox species affect various processes and the performance of DSSCs as a result. [9][10][11][12][13][14] It is generally known that the constituents in an electrolyte solution have an influence on the yield of electron injection, open-circuit voltage, electron diffusion coefficient and the rate of dye cation regeneration. 4,6 As for the effect of additives, by putting 4-tert-butyl pyridine (TBP) in an electrolyte solution, the open circuit voltage increases, while the electron injection yield decreases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, through downward shifting of the conduction band edge of the titania film, the lithium cations increase the injection yield [5][6][7][8][9][10] and 1,2-dimethyl-3-propylimidazolium (DMPIm + ) and Li + decrease the open-circuit voltage. [11][12][13][14][15][16][17] Furthermore, the ambipolar diffusion coefficients 18,19 and the rate of dye cations reduction 20 are either affected by the concentration or the species of cations. Therefore, to design the semiconductor/dye/ electrolyte interfaces for highly efficient solar cells, it is important to elucidate and understand the influence of the cations in the electrolyte on the cell performance.…”
Section: Introductionmentioning
confidence: 99%